Case Report: Osmotic Demyelination Syndrome After Transcatheter Aortic Valve Replacement: Case Report and Review of Current Literature - Jin, Xinhao; Wang, Yonggang (Frontiers in Medicine, 2022)
Background: Osmotic demyelination syndrome (ODS) is a low incidence but life-threatening neurological disorder, whose common cause is rapid overcorrection of chronic hyponatremia. Transcatheter Aortic Valve Replacement (TAVR) is a new and important therapy for patients with aortic valve stenosis. In this case, we discuss the case and literature review of a 64 years old woman who developed ODS after TAVR and this would be a matter of great concern to clinicians in the future. Case presentation: A 64 years old female patient was admitted to the hospital with 2 months of chest tightness, shortness of breath, and fatigue, aggravated 3 days. Auscultation revealed crackles in the lung fields, systolic murmur can be easily heard in aortic area. The results of echocardiography showed severe aortic stenosis. Chest x-ray showed pulmonary edema. Lab examinations showed her serum sodium is 135 mmol/L. The patient received diuretic to relieve her symptoms, but showed little benefit. Her symptoms were worse and blood pressure dropped. Then she received the emergency operation of TAVR under the support of ECMO. After the operation, urine output increased markedly and serum sodium increased from 140 mmol/L to 172 mmol/L sharply. MRI scan showed multiple lesions in the pons, which is in favor of the change of ODS. Conclusion: To date, this is the first reported case of a patient who developed ODS after receiving TAVR. In current clinical practice, diuretic is often used in aortic stenosis patients because of pulmonary edema. After a patient receives TAVR, kidney perfusion pressure quickly return to normal and with the residual effect of a high dosage diuretic, balances of fluid volume and electrolyte levels in this phase are quite fragile, must be carefully managed. If a patient has neurological symptoms/signs during this phase, ODS should be taken into consideration and MR might be undergone.